ANALYSIS OF THE GOOD AND CORRECT USE OF INDONESIAN IN NADIA OMARA'S VIDEO ENTITLED - Ertinawati, Yuni; Ananda, Aisah Diva; Wahdah, Ijma Haliza; Munawar, Zahrina Syarifatul (Media Inovasi Pendidikan dan Publikasi, 2024)
Indonesian as the official language of the country, serves not only as a means of communication, but also as a means of unifying the nation. YouTube plays an important role in the dissemination of information, including educational content. The use of good and correct Indonesian in digital content aims to maintain the credibility of the information. This research uses a descriptive analytic qualitative approach with the object of Nadia Omara's educational video entitled “MANUSIA PERTAMA YANG MENGUMANDANGKAN ADZAN DI MUKA BUMI - BILAL BIN RABAH.” The data collection technique uses video analysis techniques on the research subject. The results of this study show the extent to which language rules have been applied in educational content.